Co-composting of the biogas residues and spent mushroom substrate: Physicochemical properties and maturity assessment. (March 2019) - Meng, Xingyao; Liu, Bin; Zhang, Huan; Wu, Jingwei; Yuan, Xufeng; Cui, Zongjun
Highlights: Composting of biogas residues and spent mushroom substrate lasted 118 days. Plant growth was used to evaluate the compost maturity. Compost as tomato substrate showed better seedling quality than commercial seedling. TOC, C/N, NH4 + -N, NO3 − -N, AK and lignocellulose can be used to evaluate compost maturity. Abstract: Recycling of BR and SMS are crucial for the development of biogas industry and commercial mushroom cultivation. The seed germination test is limited to examine the maturity of compost because of lacking the effect of insoluble part on plant growth. The aim of this study was to evaluate the maturity of compost by analysis the relationship between agronomic parameters of plant growth with physicochemical parameters of compost. The thermophilic period (over 50 °C) was lasted 52 days. TOC, C/N, AP and NH 4+ -N was decreased along with composting process, while TK, TP, AK and NO3 − -N showed an opposite trend. As for seedling quality, the raw material (T0) showed the worst plant growth but the 100% compost (T1) showed better seedling quality compared with commercial seedlings. According to the analysis of Spearman correlation, the results indicated that TOC, C/N, NH4 + -N, NO3 − -N, AK and lignocellulose can be used to evaluate compost maturity.